Peran Non Performing Financing dalam Memediasi antara Equity Financing dan Debt Financing terhadap Profit Expense Ratio pada PT. Bank Syariah Mandiri - Firda Aryani; Tariza Putri Ramayanti (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
This study aims to analyze the effect of Equity Financing and Debt Financing on Profit Expense Ratio through Non Performing Financing as an intervening variable. This research was conducted at Bank Syariah Mandiri with observations for five years and the financial statements used monthly financial statements, the number of samples of research observations was 60 observations. This study finds that equity financing has a negative and insignificant effect on non-performing financing. Debt financing has a negative and significant effect on non-performing financing. Equity financing has a positive and significant effect on the profit expense ratio. Debt financing has a negative and insignificant effect on profit expense. Non-performing financing has a positive and significant effect on profit expense. Non-performing financing mediates the effect of equity financing on profit expense, which means that the independent variable of equity financing is able to directly affect the dependent variable of profit expense with or without the mediating variable. Non-performing financing does not mediate the effect of debt financing on profit expense, meaning that the independent variable of debt financing is able to directly influence the profit expense variable without involving the non-performing financing mediator variable.